Visit Transylvania! Transylvania Representations of Tourists Coming from Abroad - Pásztor, Gyöngyi; Anita Dózsa (European Journal of Social Science Education and Research, 2019)
The subject of the present study is Transylvania as a tourist destination, more precisely the analysis of what Transylvania means for the foreign tourists visiting here, and what meaning they attach to it. The timeliness of the issue is given by two factors. On the one hand the number of events with a touristic appeal has grown in the past years in Transylvania, and similarly the number of tourists has risen. On the other hand, writings that recommend Transylvania as an outstanding destination are more and more frequent in the international public sphere, in other words, it increasingly appears on the map of international tourism.